Poly(N-Isopropylacrylamide) surface-grafted ghitosan membranes as a new substrate for cell sheet engineering and manipulation - Silva, Ricardo M. P. da (2008)
The immobilization of poly(N-isopropylacrylamide) (PNIPAAm) on chitosanmembranes was performed in order to render membranes with thermo-responsive surface properties. The aim was to create membranes suitable for cell culture and in which confluent cell sheets can be recovered by simply lowering the temperature. The chitosan membranes were immersed in a solution of the monomer that was polymerized via radical initiation. The composition of the polymerization reaction solvent, which was a mixture of a chitosan non-solvent (isopropanol) and a solvent (water), provided a tight control over the chitosan membranes swelling capability. The different swelling ratio, obtained at different solvent composition of the reaction mixture, drives simultaneously the monomer solubility and diffusion into the polymeric matrix, the polymerization reaction rate, as well as the eventual chain transfer to the side substituents of the pyranosyl groups of chitosan. A combined analysis of the modified membranes chemistry by proton nuclear magnetic resonance (1H-NMR), Fourier transform spectroscopy with attenuated total reflection (FTIR-ATR) and X-ray photoelectron spectroscopy (XPS) showed that it was possible to control the chitosan modification yield and depth in the solvent composition range between 75% and 100% of isopropanol. Plasma treatment was also applied to the original chitosan membranes in order to improve cell adhesion and proliferation. Chitosan membranes, which had been previously subjected to oxygen plasma treatment, were then modified by means of the previously describedmethodology. A human fetal lung fibroblast cell line was cultured until confluence on the plasma-treated thermo-responsive chitosan membranes and cell sheets were harvested lowering the temperature.